2020
DOI: 10.1080/19476337.2020.1770336
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti-inflammatory activities of Platycodon grandiflorum seeds extract

Abstract: Antioxidant and anti-inflammatory effects of seeds and root extracts (PGSE vs. PGRE) prepared from Platycodon grandiflorum (PG) by ethanol extraction were evaluated. PGSE exhibited greater 2,2-diphenyl-l-picrylhydrazyl (DPPH•) and 2,2-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS•+) radical scavenging activities and more effectively inhibited production of nitric oxide (NO) and prostaglandin E 2 (PGE 2 ) compare to PGRE. The release of tumor necrosis factor-α (TNFα) was also decreased by 31% at 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A neutral heteropolysaccharide isolated from P. grandiflorum significantly stimulated the proliferation of RAW264.7 cells in the range of 100 μg/mL to 800 μg/mL (P < 0.05), enhanced its phagocytic ability and increased in a dose-dependent manner 35 . Ethanol extract and fermented extract of P. grandiflorum 17 significantly reduced NO concentration in LPS-induced RAW 264.7 cells in a dose-dependent manner (P < 0.05) 36 . In addition, the methanol extract of P. grandiflorum contains phenolic components, which play an anti-inflammatory role by inhibiting the production of proinflammatory cytokines IL-6, IL-12p40, and TNF-α in mouse RAW264.7 macrophages stimulated by lipopolysaccharide 37 .…”
Section: Discussionmentioning
confidence: 88%
“…A neutral heteropolysaccharide isolated from P. grandiflorum significantly stimulated the proliferation of RAW264.7 cells in the range of 100 μg/mL to 800 μg/mL (P < 0.05), enhanced its phagocytic ability and increased in a dose-dependent manner 35 . Ethanol extract and fermented extract of P. grandiflorum 17 significantly reduced NO concentration in LPS-induced RAW 264.7 cells in a dose-dependent manner (P < 0.05) 36 . In addition, the methanol extract of P. grandiflorum contains phenolic components, which play an anti-inflammatory role by inhibiting the production of proinflammatory cytokines IL-6, IL-12p40, and TNF-α in mouse RAW264.7 macrophages stimulated by lipopolysaccharide 37 .…”
Section: Discussionmentioning
confidence: 88%
“…Ultimately, oxidative stress might aggravate the production and aggregation of Aβ to promote neuroinflammation and neurodegeneration, leading to a vicious cycle of pathogenesis in AD. Numerous studies have previously demonstrated the antioxidative properties of PGE on various cell lines [ 17 , 72 , 73 ]. This compelling data allows us to deduce that the anti-amyloid, anti-inflammatory, and neuroprotective activities of PGE may eradicate the vicious circle induced by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Platycodon grandiflorum (PG), one of the well-known traditional herbal remedies found in East Asia, including China, Korea, and Japan, has been widely used because it not only exhibits valuable bioactive effects but also does not have toxicity and adverse effects [ 12 ]. A number of studies have reported that PG has a variety of bioactive functions, including antioxidant, anti-inflammatory, anti-obesity, anti-diabetic, and anti-tumor activities [ 13 , 14 , 15 , 16 , 17 ]. In addition, PG shows considerable beneficial effects, such as anti-cholesterol effects, reduced levels of low-density lipoproteins, and increased coronary blood flow in the metabolic and cardiovascular systems [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…DPPH and ABTS radical scavenging methods are frequently used to assess the antioxidant activity of various food products. The half-inhibitory concentration of Jiegeng for DPPH and ABTS free radicals is 4.07 mg/mL and 2.10 mg/mL, while the half-inhibitory concentration of P. grandiflorum seeds is only 0.13 mg/mL and 0.04 mg/mL, indicating that the seeds of P. grandiflorum have stronger antioxidant activity than the Jiegeng ( Kim, Yoon, Lee, & Imm, 2020 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 97%